Mechanism and role of H. pylori CagA-induced NLRP3 inflammasome in gastric cancer immune cell infiltration - Chuandan Wan; Ping Wang; Yeqiong Xu; Yanping Zhu; Huanhuan Chen; Xuexian Cao; Yulan Gu (Scientific Reports)
Abstract The high incidence of gastric cancer in China is strongly associated with widespread Helicobacter pylori infection. While the bacterium’s role in gastric cancer initiation and progression is well-established, the precise molecular mechanisms remain incompletely characterized. Current clinical challenges include limited early detection methods and poor therapeutic efficacy in advanced stages. Immune checkpoint inhibitors have shown clinical benefits in subsets of patients; however, many exhibit primary resistance or acquire secondary resistance, though the mechanisms underlying this resistance remain poorly understood. Emerging evidence suggests that H.pylori infection may remodel the tumor microenvironment, thereby influencing gastric cancer pathogenesis, progression, and therapeutic response. This study investigates the CagA virulence factor-mediated signal-transduction pathway during H.pylori infection, elucidating its role in NLRP3 inflammasome activation and subsequent pathological modulation of gastric epithelial cells. We further analyze correlations between NLRP3 expression and clinicopathological features, evaluating its prognostic value in predicting clinical outcomes. Additionally, we examine how this signaling axis regulates immune cell infiltration and modulates molecular pathology within the tumor immune microenvironment, laying a foundation for novel diagnostic and immunotherapeutic strategies.